2023
DOI: 10.1021/acsanm.3c01122
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastable Gold–Copper Nanoclusters on Nitrogen-Doped Graphene Quantum Dots for Selective Electrochemical and Fluorescence Sensing of Glycine

Saisree S,
Dhrishya V,
Sandhya Karunakaran Yesodha

Abstract: In this work, we present an ultrastable gold−copper nanocluster on nitrogen-doped graphene quantum dot (AuCuNC@N-GQD), with a stability of ≥1 year, achieved through a galvanic exchange process, which displayed intense solid-and solution-state near-infrared emission. Furthermore, the NC exhibited selective and dual sensing of glycine (GLY) through (nonenzymatic) electrochemical (EC) and fluorescence methods, which is assigned to the unique combination of the strong emission and conducting properties of Au−CuNC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 57 publications
(101 reference statements)
0
2
0
Order By: Relevance
“…Consequently, the metal atoms with lower oxidation potentials present on the clusters' surface undergo oxidation, leading to the formation of ions. Conversely, the metal ions possessing greater oxidation potentials undergo reduction and subsequently replace the oxidized metal atoms on the surface of the metal clusters [27]. In this experimental procedure, the addition of HauCl4 to BSA-AgNCs results in the substitution of some Ag atoms on the surface with Au atoms.…”
Section: Formation Of Bimetallic Gold-silver Nanoclustersmentioning
confidence: 99%
“…Consequently, the metal atoms with lower oxidation potentials present on the clusters' surface undergo oxidation, leading to the formation of ions. Conversely, the metal ions possessing greater oxidation potentials undergo reduction and subsequently replace the oxidized metal atoms on the surface of the metal clusters [27]. In this experimental procedure, the addition of HauCl4 to BSA-AgNCs results in the substitution of some Ag atoms on the surface with Au atoms.…”
Section: Formation Of Bimetallic Gold-silver Nanoclustersmentioning
confidence: 99%
“…31 Transition metal cluster-decorated graphene substrate turned out to be promising for applying it as an electrochemical sensor. 32 , 33 Gold–copper clusters deposited on nitrogen-doped graphene-based quantum dots were demonstrated by Saisree et al 34 to be selective materials for detecting glycine under electrochemical conditions, while they also showed that its copper decorated analogues are possible candidates for sensing dopamine, serotonin, or nicotine. 35 Yang et al investigated the tunability of palladium decorated graphene, which can be used as formaldehyde detector.…”
Section: Introductionmentioning
confidence: 99%